2017
DOI: 10.1108/ijshe-05-2015-0100
|View full text |Cite
|
Sign up to set email alerts
|

Using module-based learning methods to introduce sustainable manufacturing in engineering curriculum

Abstract: Purpose Sustainable manufacturing may be defined as the creation of manufactured products that use processes that are non-polluting, conserve energy and natural resources, and are economically sound and safe for employees, communities and consumers. Recently, there have been several industrial and governmental endeavors to launch sustainable manufacturing initiatives. To support such initiatives and to prepare the next generation of scientists and engineers, academic institutions have a responsibility to intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These challenges require an organizational culture focused on innovation and learning, as well as academic knowledge translation into practice to facilitate the implementation of both emerging technologies and sustainable practices. Such expertise could be achieved with the use of new training methods to introducesustainable manufacturing concepts and using I4.0 skills training to improve the understanding of emerging technologies and related concepts [150].…”
Section: A Industry 40 and Sustainable Manufacturingmentioning
confidence: 99%
“…These challenges require an organizational culture focused on innovation and learning, as well as academic knowledge translation into practice to facilitate the implementation of both emerging technologies and sustainable practices. Such expertise could be achieved with the use of new training methods to introducesustainable manufacturing concepts and using I4.0 skills training to improve the understanding of emerging technologies and related concepts [150].…”
Section: A Industry 40 and Sustainable Manufacturingmentioning
confidence: 99%
“…Case studies designed by the Rocky Mountain Institute (RMI) were introduced to the engineering curricula and the results of the pilot study revealed a strengthened understanding of the whole system design concept (Blizzard et al, 2012). Sustainable Manufacturing Advances in Research and Technology, an international research network, generated case studies for incorporating sustainability manufacturing in the engineering curriculum in the US (Sengupta et al, 2017).…”
Section: Developments In Teaching Techniques/pedagogical Approachesmentioning
confidence: 99%
“…They found that course organisation, student difficulties working in multidisciplinary teams, and limited student engagement in projects are barriers in such courses. Several authors presented case studies of teaching sustainable engineering in single-university environment by multidisciplinary approach and embodying sustainability in other engineering curriculum (Perdan et al, 2000), such as chemical (Glassey and Haile, 2012) and mining and petrochemical (Shields et al, 2014), or by presentation of sustainable manufacturing educational case studies (Sengupta et al, 2017). Stansinoupolos et al (2013) presented an integrated approach to sustainable engineering based on the application of systems engineering.…”
Section: Introductionmentioning
confidence: 99%